DNA methylation and demethylation events during meiotic prophase in the mouse testis. - Trasler, J M (1990)
The genes encoding three different mammalian testis-specific nuclear chromatin proteins, mouse transition protein 1, mouse protamine 1, and mouse protamine 2, all of which are expressed postmeiotically, are marked by methylation early during spermatogenesis in the mouse. Analysis of DNA from the testes of prepubertal mice and isolated testicular cells revealed that transition protein 1 became progressively less methylated during spermatogenesis, while the two protamines became progressively more methylated; in contrast, the methylation of beta-actin, a gene expressed throughout spermatogenesis, did not change. These findings provide evidence that both de novo methylation and demethylation events are occurring after the completion of DNA replication, during meiotic prophase in the mouse testis.